WOUNDS OF HISTORY: MEMOIR REFLECTIONS ON THE ARMENIAN GENOCIDE IN ITALY - Haroutyunian, Sona (Armenian Folia Anglistika, 2024)
This paper delves into the memoirs of Armenian Genocide survivors in Italy, examining how, despite the immense emotional toll, these individuals eventually found the strength to document their suffering. It explores the ways in which they navigated the silence surrounding their trauma, ultimately putting pen to paper to share the horrors they witnessed. These memoirs serve as crucial testimonies, offering the world invaluable insights into the atrocities of the genocide and ensuring that these stories, once buried in silence, are preserved for future generations. The paper also considers the cultural and psychological barriers that survivors faced, as well as the profound importance of memory in shaping historical understanding. The idea of ​​this article was born in me in connection with the 90th anniversary of the novel The Forty Days of Mount Musa by Franz Werfel, a great supporter of humanity and peace and an unwavering critic and rejecter of genocidal acts because the lessons conveyed to us by the survivors’ memoirs are instructive and deserve attention.